"There is Subjectivity, There is Bias": Teacher Candidates' Perceptions of Equity in Data Literacy for Teaching. Issue 3 (2nd July 2020) - Whitesides, Heather; Beck, Jori S.
Abstract: Research on equity in data literacy for teaching has lagged yet is of critical importance to ensuring new teachers are prepared to serve diverse students. Our multiple case study conveyed four elementary teacher candidates' understandings of this construct and their reaction to instruction in this domain. Data collection included interviews, item analysis, and concept maps. Our participants developed a broader view of data by the end of the course, but often did not recognize inequitable data practices like tracking which conveys a misalignment between beliefs and practices. We explored implications for policy and practice based on our findings.